Gut microbial communities and pathogens infection in New Zealand bumble bees (Bombus terrestris, Linnaeus, 1758). Issue 2 (3rd July 2021) - Felden, Antoine; Baty, James W.; Lester, Philip J.
ABSTRACT: The gut microbiome is an important component of bee health. Previous research around the globe indicated that bee gut microbiome can be affected by the presence of pathogens. We surveyed for the presence of three specific pathogens in populations of the buff-tailed bumble bee, Bombus terrestris (Linnaeus, 1758), across New Zealand. The pathogen Crithidia bombi was the most prevalent and widespread pathogen across the studied sites, with prevalence ranging from 30 to 100% of the bees examined. Nosema bombi was, however, only found in North Island sites. The Deformed wing virus was detected in bumble bees at all the sites except one (Twizel in the South Island) with prevalence ranging from 0 to 60%. The B. terrestris gut microbiome and the associated pathogens from two contrasting locations were studied. Bacteria such as Snodgrassella alvi and Lactobacillales were observed. We also found that infections with C. bombi were associated with more diverse, distinct gut microbiome perhaps indicating disruptions of gut microbe communities that contribute to impair bumble bees' health.